Problematika Pendidikan Islam Anak Usia Dini - Kiki Utami (STAI Ma'had Aly Al-Hikam Malang, 2025)
Early childhood aged 0-6 years have a complex and very unique phase of growth and development. Its growth and development has developed very rapidly and cannot be repeated in the future. At an early age it is also said that the golden age, where children at an early age can easily imitate and absorb various knowledge in their environment, both positive and negative, so that at an early age it is very good to be given positive knowledge. The aim of the research is to understand the Islamic problems of early childhood in learning at school. This research uses a qualitative method with a library research approach or literature research, with data collection tools in the form of primary data and secondary data such as observation of problematic books on the development of early childhood education and secondary data supporting data that is relevant to this research, such as books, magazines, documents and journal articles about research directly. The technical analysis of this research is in the form of content analysis techniques or content analysis. Based on the research results, it shows that ways to deal with the problems of early childhood Islamic education in learning include 1) learning methods & strategies, infrastructure, learning media, 3) teacher competency.